POTRET NOVEL INDONESIA-PAPUA TAHUN 2000-2012 (SEBUAH INVENTARISASI) - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2019)
Novel is the prose that written based on social context as human mimetic. Indonesian novel are the prose was written by using Indonesian language. This research discuss about Indonesian novel that tell about Papua in 2000-2012. That novel can be told about its ethnics, its people, its cultures, or its nature. This research uses descriptive methods and collecting data by library research. They are seven Indonesian novel has written in 2000-2012. Those novels told about Papuan. Those novels are: Namaku Teweraut by Ani Sekarningsih (2000); Kapak by Dewi Linggasari (2005); Sali: Kisah Seorang Wanita Suku Dani by Dewi Linggasari (2007); Mawar Hitam Tanpa Akar by Aprila R.A. Wayar (2009); Tanah Tabu by Anindita S. Thayf (2009); Elang by Kirana Kejora (2009); and Istana Pasir by Dewi Linggasari (2010).